Acceptorless and Base‐Free Dehydrogenation of Alcohols Mediated by a Dipyridylamine‐Iridium(III) Catalyst. Issue 28 (16th July 2020) - Jayaprakash, Harikrishnan; Guo, Liwei; Wang, Shengdong; Bruneau, Christian; Fischmeister, Cédric
Abstract : Several dipyridylamine‐Ir III and dipyridylamine‐Ru II complexes have been evaluated in the acceptorless dehydrogenation of alcohols in the absence of base additives. Iridium catalysts were found superior to ruthenium complexes, and the nature of the bridging nitrogen in dipyridylamine ligands was also evidenced as a key parameter. Catalytic reactions were conducted in toluene, but more sustainable solvents such as anisole and p ‐cymene were found suitable for this transformation. Abstract : The acceptorless and base‐free dehydrogenation of secondary alcohols is achieved with an iridium(III) catalyst bearing a dipyridylamine ligand.